Contradictions Of Civil Law With Islamic Law And Its Implication On A Muslim’s Responsibility - Siti Khadijah Binte Mahfuh (Audito Comparative Law Journal (ACLJ), 2022)
This paper aims to understand the implications of civil law on a Muslim’s responsibility resulting from contradictions between civil law and Islamic law. The research uses the qualitative method. This paper looks at general laws that allow Muslims not to practice Islamic law. The study shows that law acts contradict Islamic practice. Thus, every Muslim should not disregard his responsibilities to fulfill worldly desires.